Redo mitral valve surgery 15 years after bioprosthetic valve implantation in a patient with hepatic and cardiac comorbidities - Khan, Omar S.; Jahan, Sharmin; Haque, Rezwanul; Barua, Sumit; Nuruzzaman, Mostafa (International Journal of Research in Medical Sciences, 2025)
Redo mitral valve surgery poses significant technical and clinical challenges, especially in patients having a third reoperation. These cases are associated with increased operative threat due to adhesions, previous sternotomies, and limited surgical exposure. With significant advancements in surgical techniques, perioperative care, and patient selection, successful outcomes can still be achieved. We report the case of a 47-year-old male with a complex cardiac history, including surgical atrial septal defect (ASD) closure and prior bioprosthetic mitral valve replacements, who presented with symptomatic structural valve deterioration and progressive heart failure. A third-time redo mitral valve replacement was performed via median sternotomy, using femoral cannulation. Intraoperative findings included extensive adhesions and prior prosthetic valve degeneration. The postoperative course was notable for transient low cardiac output and arrhythmia management; however, the patient eventually recovered well and was discharged on the 10th postoperative day.